2018
DOI: 10.1016/j.cjtee.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Non-microsurgical skin flaps for reconstruction of difficult wounds in distal leg and foot

Abstract: PurposeTo express the versatility of a variety of non-microsurgical skin flaps used for coverage of difficult wounds in the lower third of the leg and the foot over 4 years period. Five kinds of flaps were used. Each flap was presented with detailed information regarding indication, blood supply, skin territory and technique.MethodsAltogether 26 patients underwent lower leg reconstruction were included in this study. The reconstructive procedures applied five flaps, respectively distally based posterior tibial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 42 publications
0
9
0
2
Order By: Relevance
“…9 El trauma del miembro o la patología vascular periférica afectan el flujo sanguíneo del miembro complicando aún más el panorama. 10 Gracias a varios estudios anatómicos se han revelado arterias perforantes confiables, como las de la arteria tibial posterior [11][12][13] fácilmente identificables con ecografía Doppler.…”
Section: Resultsunclassified
“…9 El trauma del miembro o la patología vascular periférica afectan el flujo sanguíneo del miembro complicando aún más el panorama. 10 Gracias a varios estudios anatómicos se han revelado arterias perforantes confiables, como las de la arteria tibial posterior [11][12][13] fácilmente identificables con ecografía Doppler.…”
Section: Resultsunclassified
“…The lack of knowledge of the local tissue vascularization pattern has been the main cause of disappointment with local fasciocutaneous flaps [6]. The situation is even more complicated when the blood flow is affected by the limb trauma or the peripheral vascular pathology [5]. Reliable perforator arteries have been known thanks to several anatomic studies, such as those from the posterior tibial artery [13,14] which are easily identified by Doppler sonography.…”
Section: Discussionmentioning
confidence: 99%
“…14,21,32,37,[39][40][41][42][43][44][45][46] The third most common reason why free tissue transfer was not used was anatomic limitation (28 of 51 publications, n ¼ 170 of 322, 52.8% of patients) described in a variety of ways: no recipient vessels, inadequate vasculature, poor vascular supply, severe arterial injury, vascular damage, extensive zone of injury, lack of vasculature, one vessel run-off, or slight variations on the same language. 6,12,15,19,20,36,37,39,41,42,45,[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] Prior free flap failure was cited as the indication for cross-leg flap in six publications (n ¼ 27 of 250, 10.8% of patients). 12,39,49,56,63,64 Comorbidities prohibiting free tissue transfer (n ¼ 19 of 250, 7.6% of patients), 12,…”
Section: Indications For Not Performing Free Tissue Transfermentioning
confidence: 99%
“…Various names were used to describe flaps, as there was not a consistent nomenclature. Fasciocutaneous was the most common broad classification, mentioned in 31 publications 6,11,12,[15][16][17][18][20][21][22]25,28,30,[32][33][34][36][37][38][42][43][44][45][46]49,50,56,57,59,63,65 including 273 patients (n ¼ 273 of 318, 85.8%), with muscle or myocutaneous second most common, 20,29,30,37,39,44,47 including 45 patients (n ¼ 45 of 318, 14.2%). Other flap types were not described according to common nomenclature, and it was impossible to tell if they were fasciocutaneous or musculocutaneous (n ¼ 83).…”
Section: Characteristics Of Transferred Tissuementioning
confidence: 99%
See 1 more Smart Citation